The Differences of Respiratory Symptoms and Pulmonary Impairment between Exposure and Unexposured Areas by Dust from Semen Padang Factory - Dian Citra; Irvan Medison; Sabrina S Ermayanti (Jurnal Respirologi Indonesia, 2018)
Background: The cement factories have a waste product such as dust that had negative impact on respiratory system. The aims of this study is to investigate the differences of respiratory symptoms and pulmonary impairment between exposure and unexposured region by dust from Semen Padang factory. Methods: Cross sectional study of 282 subjects from exposure and unexposure areas in Semen Padang factory. This study was held in March 2016 - July 2017. Dust levels were assessed at both areas. Respiratory symptoms were assessed by interviews and quistionnaires. Lung function was measured by spirometry examinations. The variables between both groups were analyzed. Results: The daily dust level of exposure area close to three folds than unexposure area (150μg/Nm 3 vs 53,50 μg/Nm 3) yet still in save level that assigned by regulation. There were 282 subjects from both areas which consist of 67 men and 74 women for each area. There were no differences in respiratory symptoms included chest pain (0% vs 0,7%, P=1,00), productive cough (4,3% vs 2,1%, P=0,5), cronic cough (4,3% vs 2,1% ,P=0,5) and breathlessness (5,7% vs 5% ,P=1,00). The proportion of pulmonary impairment not difference between two areas (P=0,053). Concusions: Both area had dust level below up level assigned by regulation. There were no differences in respiratory symptoms and pulmonary impairment at exposure area and unexposure area. Breathlessness is most common symptom.